2006
DOI: 10.1007/s10557-006-8283-x
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Relevance of Low-Density-Lipoproteins Size Modulation by Statins

Abstract: The predominance of small, dense low density lipoproteins (LDL) has been accepted as an emerging cardiovascular risk factor by the National Cholesterol Education Program Adult Treatment Panel III; in fact, LDL size seems to be an important predictor of cardiovascular events and progression of coronary heart disease. Several studies have also shown that the therapeutical modulation of LDL size is of great benefit in reducing the risk of cardiovascular events. Hypolipidemic treatment is able to alter LDL subclas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
49
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 90 publications
(181 reference statements)
2
49
0
7
Order By: Relevance
“…It is known that the therapeutical modulation of low HDL-cholesterol and high triglycerides significantly reduce cardiovascular risk [3] and lipid-lowering agents are also effective in reducing levels of small, dense LDL [26][27][28]. Dietary management is also of importance in such category of high-risk subjects [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the therapeutical modulation of low HDL-cholesterol and high triglycerides significantly reduce cardiovascular risk [3] and lipid-lowering agents are also effective in reducing levels of small, dense LDL [26][27][28]. Dietary management is also of importance in such category of high-risk subjects [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, 12 responders and two non-responders were treated with lipid-lowering agents, and most of these patients (11/12 responders and 1/2 non-responders) used HMG-CoA reductase inhibitors (statins). Several studies have shown that low-density lipoprotein (LDL) size rather than plasma LDL level is more correlated with insulin resistance and eventual progression of coronary heart disease (Rizzo and Berneis 2006). Although the efficacy of modifying LDL size is different among agents (fluvastatin and atorvastatin seem to be much more effective agents than pravastatin and simvastatin), statins moderately lower all LDL subclasses, and, somehow, this process seems to make metformin more effective.…”
Section: Discussionmentioning
confidence: 99%
“…Since atherogenic dyslipidemia generally appears prior to clinical manifestations of MetS, treatment strategies have focused on the pharmacological approach, with reports that patients with atherogenic dyslipidemia may benefit from statins 19) . Moreover, different statins have been described to have different effects on sd-LDL 8) . The aims of the present study were to compare the outcomes of different statin treatments used to lower LDL-C in patients with MetS on sd-LDL, which is one of the most important components of dyslipidemia in these patients, and to test whether this can be regarded as a class effect.…”
Section: Discussionmentioning
confidence: 99%
“…Novel statins with more potent LDL-C-lowering effects 20) are known to demonstrate partial differences in their non-LDL effects compared to previous statins 8) . Ai et al 21) found, in 271 hyperlipidemic patients, that 6 weeks of maximal-dose rosuvastatin (40 mg/day) and atorvastatin (80 mg/day) treatments provided significant and beneficial change throughout the lipoprotein particle spectrum, and that rosuvastatin was significantly more effective in reducing sd-LDL levels than atorvastatin ( 53% vs. 46%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation